Determinants of Net Interest Margin in Conventional Commercial Banking: A Fixed Effect Model - Safitri, Erika Zain; Zahrah, Zahrah; Saputra, Sahdan; Anwar, Mohammad Ziad (Target : Jurnal Manajemen Bisnis, 2024)
Banking is a business entity that collects funds from the public in the form of deposits and distributes them to the public in the form of loans and other services to improve the lives of many people. This study aims to analyze the influence of various factors such as capital adequacy, credit risk and bank size on the net interest margin of conventional banks in Indonesia. The method used in this study was associative quantitative, and secondary data in this study was obtained from the annual financial statements of several conventional banks in Indonesia during the period 2018-2022. Data analysis was conducted using panel data regression analysis to test the effect between independent variables consisting of capital adequacy ratio (CAR), non-performing loans (NPL), and bank size (Size) on net interest margin (NIM). The data was processed using E-Views 12. The results of this study indicate that only capital adequacy has a positive and insignificant effect on NIM, while NPL and bank size have a negative and significant effect on NIM. The findings of this study imply that in order to enhance NIM, companies can optimize CAR, thereby attaining optimal profits and minimizing investment risk. The results of this study also contribute as a reference and an overview of the factors that influence NIM in conventional commercial banks before investing.